Understanding the Influence of Corporate Social Resposibility on Firm Performance: Perception of Employee - Indraguna Kusumabrata (Indonesian Management and Accounting Research, 2019)
The purpose of this paper is to examine the perception of Corporate Social Responsibility (CSR) on firm performance with the role of one of the potential mediators, namely job satisfaction. The main limitation of the study is the limited size of the total sample and only in one company so the result could not be generalized. This study shows how CSR is related to the performance of the company. This study based on data from 115 employees. The construct was measured by questionnaire. The results show a positive relationship between social responsibility and firm performance based on employee perceptions. By revealing the importance of social responsibility activities to corporate performance, this study contributes to the area of social responsibility research.